Prognostic biomarker soluble ST2 exhibits diurnal variation in chronic heart failure patients - Sandra Crnko; Markella I. Printezi; Tijn P.J. Jansen; Laurynas Leiteris; Manon G. van derMeer; Hilde Schutte; Martijn vanFaassen; Bastiaan C. duPré; Nicolaas deJonge; Folkert W. Asselbergs; Carlo A.J.M. Gaillard; Hans Kemperman; et al. (ESC Heart Failure)
Abstract Aim Soluble suppression of tumorigenicity‐2 (sST2) is a strong prognostic biomarker in heart failure. The emerging understanding of circadian biology in cardiovascular disease may lead to novel applications in prognosis and diagnosis and may provide insight into mechanistic aspects of the disease–biomarker interaction. So far, it is unknown whether sST2 exhibits a diurnal rhythm. Repeated measurements of sST2 may aid in clinical decision making. The goal of this study was to investigate whether sST2 exhibits diurnal variation in patients with heart failure with reduced ejection fraction (HFrEF) and in control subjects, thereby enhancing its diagnostic and prognostic values. Methods and results The study comprised 32 subjects: 16 HFrEF patients and 16 controls. Blood was collected at seven subsequent time points during a 24 h time period. sST2, N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP), melatonin, and cortisol were measured from serum. Peak values of sST2 clustered at daytime (modal value: 5 p.m.) in 87.6% of all subjects (81.3% of patients, P = 0.021; 93.8% of controls, P = 0.001), and minimum concentrations at night‐time (modal value: 5 a.m.) in 84.4% (87.5% of patients, P = 0.004 81.3% of controls, P = 0.021). A cosinor analysis of mean normalized sST2 values revealed significant cosine shaped 24 h oscillations of patients (P = 0.026) and controls (P = 0.037). NT‐proBNP in contrast did not show a diurnal rhythm, while melatonin and cortisol patterns were intact in all subjects. Conclusions sST2 exhibits a diurnal rhythm with lower values in the morning than in the late afternoon. This new insight could lead to refinement of its diagnostic and prognostic values through specified and consistent sampling times with repeated measurements. For example, by measuring sST2 during the afternoon, when levels are at their highest, false negatives on prognosis prediction could be avoided.